Client-side adaptation: An approach based in reutilization using transversal models - Firmenich, Sergio (2010)
Improving navigability in Web applications is essential for applications success. Our research aims to improve the user experience by applying novel techniques such as concern-sensitive navigation. Concern-sensitive navigation allows enriching Web pages with content related to the context in which they are accessed. In previous works, we showed how this technique can be applied during the development process; at present we are working in a client-side adaptation approach to apply concern-sensitive navigation to existing applications. This approach is open to other adaptation kinds which are illustrated in this position paper. We also outline a set of tools we are developing to simplify the process of adaptation.